Repercussions of Chinese land deals in South America: vectors of mobilization and domestic institutions - Søndergaard, Niels (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: The article analyses domestic reactions to Chinese land deals in Brazil, Argentina and Bolivia, and how such attempts have affected these countries’ regulatory framework for foreign land acquisitions. Materials and Methods: Mobilizations against these deals are examined with focus on their internal composition of social forces, and the framings which they produce in order to press for regulatory restrictions. Results: The emergence of protest in Argentina and Brazil, relative to the lack of opposition in Bolivia, is explained through a most similar case design, emphasizing differences in the rural socio-economic structure and composition of capital within the agricultural sector as central explanatory factors, accounting for the variation of the outcome in the cases examined. Discussion: With point of departure in the debate about global land investment, the article contributes to understanding how foreign investment is accommodated within different modes of commodity dependent development. KEYWORDS: Land governance; South America; Land conflict; China; Agribusiness.